2
$\begingroup$

P(x) is a polynomial with roots x1,x2,x3...xn and P'(x) is its derivative. So can anyone explain how P'(x) can be factored as shown in the screenshot, using the roots of P(x)?!enter image description here

$\endgroup$
  • 1
    $\begingroup$ This follows from the usual product rule. Try writing it out for a cubic, you'll see the pattern. $\endgroup$ – lulu Jan 22 at 17:38
2
$\begingroup$

Let $f_k(x) = x-x_k$, note that $f_k'(x) = 1$.

Since $P(x) = f_1(x) f_2(x)\cdots f_n(x)$, the product differentiation rule gives $P'(x) = f_1'(x) f_2(x)\cdots f_n(x) + f_1(x) f_2'(x)\cdots f_n(x) + \cdots + f_1(x) f_2(x)\cdots f_n'(x)$, or $P'(x) = f_2(x)\cdots f_n(x) + f_1(x) f_3(x)\cdots f_n(x) + \cdots + f_1(x) f_2(x)\cdots f_{n-1}(x)$.

$\endgroup$
  • 1
    $\begingroup$ Ohh I get it now, I just never used the product rule for more than 2 factors. Thanks!!! $\endgroup$ – Happiness Is The Truth Jan 22 at 18:31
2
$\begingroup$

$P(x)=\prod (x-x_i)$ and so $\ln P(x)=\sum \ln (x-x_i)$

Differentiate w.r.t. $x$

$$\frac{P'(x)}{P(x)}=\sum \frac{1}{x-x_i}$$

$\endgroup$
1
$\begingroup$

So you want to prove $${P'(x)\over P(x) } = {1\over x-x_1}+{1\over x-x_2}+...+{1\over x-x_n}$$

but this is the same as $$(\ln P(x))' = (\ln(x-x_1)+\ln(x-x_2)+...+\ln(x-x_n))'$$

or $$(\ln P(x))' = (\ln(x-x_1)(x-x_2)...(x-x_n))'$$ or $$\ln P(x) = \ln(x-x_1)(x-x_2)...(x-x_n)+const$$

If we write $a= e^{const}$ i.e. $const = \ln a$ we get $$p(x) =a(x-x_1)(x-x_2)...(x-x_n)$$

Now read this from down to up and thus a conslusion.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.